Comparative Efficacy and Safety of Limus-Eluting Stents in Acute Coronary Syndrome in Asian People: A Network Meta-Analysis and Bioinformatics Study - Prazeva, Marista; Hendrawan, Adha; Habiby, Farhan (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Evidence on the relative performance of limus-eluting stents (LES) in acute coronary syndrome (ACS) among Asian patients is mixed, and formal rankings with biological context are limited. We compared LES and examined drug-specific mechanisms. Methods: Randomized trials of ACS patients undergoing PCI with 12-month outcomes were identified systematically. A frequentist network meta-analysis combined 19 trials (n=25,642) to estimate odds ratios (ORs) for major adverse cardiovascular events (MACE) and mortality and to derive treatment ranks (P-scores). Bioinformatics included molecular docking to FKBP12/mTOR/VEGFR2, ADMET/toxicity prediction, protein–protein interaction networks, and KEGG/GO enrichment. Results and Discussion: All limus stents lowered 12-month MACE versus paclitaxel (ZES 0.46 [0.34–0.64]; EES 0.55 [0.41–0.71]; SES 0.58 [0.46–0.72]; BES 0.60 [0.42–0.86]). Differences within the limus class were small (ZES vs SES 0.80 [0.62–1.06]). Rankings favored zotarolimus (SUCRA 0.94), followed by everolimus (0.64) and sirolimus (0.50); biolimus (0.42) ranked below, and paclitaxel was lowest. Mortality did not differ. Docking indicated stronger binding of limus agents to FKBP12/mTORC1 than paclitaxel, and toxicity models suggested a wider safety margin for limus agents (everolimus LD50 2,500 mg/kg; paclitaxel 134 mg/kg). Enrichment analyses highlighted PI3K–Akt/mTOR pathways relevant to vascular healing. Conclusion: In Asian ACS, LES outperform paclitaxel at 12 months. Zotarolimus ranks first, with everolimus and sirolimus performing comparably. The clinical ranking aligns with predicted target engagement and toxicity profiles.